Beyond territorial contiguity: Issues at stake in democratic militarized interstate disputes. - Mitchell, Sara McLaughlin; Prins, Brandon C. (International Studies Quarterly)
Examines the theoretical relationship between regime type, issues and militarized conflict, based on data on disputes between democratic states during 1946 to 1992. Identification of issues in dispute; Ability of democracies to remove territory as an issue; Lack of resolution in the post-World War II period.